Papal Power and Protection in the Shebet Yehudah. (17th December 2015) - Rist, Rebecca
Abstract : The sixteenth‐century Shebet Yehudah is an account of the persecutions of Jews in various countries and epochs, including their expulsion from Spain in the fifteenth century. It is not a medieval text and was written long after many of the events it describes. Yet although it cannot give us a contemporary medieval standpoint, it provides important insights into how later Jewish writers perceived Jewish–papal relations in the thirteenth, fourteenth, and fifteenth centuries. Although the extent to which Jewish communities came into contact either with the papacy as an institution or the actions of individual popes varied immensely, it is through analysis of Hebrew works such as the Shebet Yehudah that we are able to piece together a certain understanding of Jewish ideas about the medieval papacy as an institution and the policies of individual popes. This article argues that Jews knew only too well that papal protection was not unlimited, but always carefully circumscribed in accordance with Christian theology. It is hoped that it will be a scholarly contribution to our growing understanding of Jewish ideas about the papacy's spiritual and temporal power and authority in the Later Middle Ages and how this impacted on Jewish communities throughout medieval Europe.